La crisis de la vida pública y su incidencia en el subdesarrollo: incursiones en torno a la debilidad de las instituciones y del Estado en México / The crisis of public life and its incidence in underdevelopment: incursions around the weakness of institutions and the State in Mexico - ENRÍQUEZ PÉREZ, Isaac; FLORES SANDOVAL, Rubén Darío (Utopía y Praxis Latinoamericana, 2019)
RESUMEN A través del presente artículo brindamos un análisis panorámico sobre la génesis, la naturaleza y el sentido histórico de la “crisis de lo público” experimentada en México, reconociendo un contexto histórico contemporáneo signado por un Estado mexicano que tiende a perder el control sobre amplias porciones del territorio nacional, y en el que una serie de (contra)poderes fácticos le disputan la hegemonía y se esfuerzan –en no pocos casos– por erigir una parainstitucionalidad estatal que define cursos de acción más allá de la legalidad establecida. Se trata de comprender la relación entre el espacio público, los (contra)poderes y su construcción, las funciones de un Estado fragmentado, y la dialéctica desarrollo/subdesarrollo en México. ABSTRACT This paper offers an overview of the genesis, nature and historical significance of the crisis of public life in early 21st century Mexico. The analysis begins by recognizing a historical context where many areas of the Mexican territory lie beyond state control, and where a number of counterpowers challenge and dispute the state’s legitimate monopoly of force and hegemony. The paper characterizes the evolution of public life in 20th century Mexico and briefly compares recent transformations in this sphere with similar developments taking place in other parts of the globe. The paper goes on to argue that the erosion of public life and its attendant crisis of civic culture have as their background the deep-rooted social inequalities and the conditions of underdevelopment that characterize Mexican reality. In turn, underdevelopment and inequality are expressed, and deepened, by the fragility of Mexican institutions and the Mexican state’s state of crisis. Thus, the paper seeks to apprehend the interconnections between public life, state fragmentation, and the development/underdevelopment dialectic in early 21st century Mexico.